Identification of starting points to promote health and wellbeing at the community level - a qualitative study - Jennifer Hilger-Kolb; Claudia Ganter; Maren Albrecht; Catherin Bosle; Joachim E. Fischer; Laura Schilling; Claudia Schlüfter; Maria Steinisch; Kristina Hoffmann (BMC, 2019)
Abstract Background As health is influenced by the social, economic and environmental conditions in which individuals live, local communities are an ideal setting to promote health and wellbeing. However, up to now various health promotion interventions at the community level have had limited success, perhaps related to an incomplete understanding of local contexts and priorities. We therefore aimed to develop a broader and deeper understanding of topics or issues that were most salient to residents of a South-West German community by exploring their perceptions of needs, challenges, barriers and existing resources related to health and well-being. Methods As an initial step of a multi-year community-based participatory research project, we conducted semi-structured interviews with key informants (n = 30) from various community settings (e.g., child care, elderly care, businesses, non-profit organizations, village councils, and local government). The terms "health" and "wellbeing" were included in the stem of each question in the semi-structured interview guide to enable a focus on related perceived needs, challenges, barriers and existing resources. Interviews were audiotaped, transcribed verbatim and analyzed using qualitative content analysis techniques. Results Themes emerging from our interviews appeared to center primarily in three distinct areas: natural resources and built environment, access to services, and social cohesion including subthemes on the importance of social engagement and volunteerism, sense of community, and shared identity. Conclusions That health and wellbeing were not identified explicitly as a priority by key informants suggests that these should not be presented as the primary focus of a community-wide initiative. Instead themes with a higher priority should be addressed in ways that can lead to better health and wellbeing as a secondary goal.